"Exul ad externas ultro se contulit oras". Esilio e memoria classica nelle 'Epistole metriche' di Albertino Mussato (Quaderni di Gargnano, 2018)
In the context of a general presentation of the metrical epistles of Albertino Mussato, the paper pays particular attention to the letters referring to the painful political exile of Mussato, a Paduan pre-humanist who spent the last years of his life in Chioggia, during which time he wrote to Bonincontro da Mantova and Guizzardo da Bologna, tow of the leading rhetoricians and grammarians of their day. After a brief review of Mussato’s political career in Padua, which ended with his banishment to the nearby city of Chioggia, the paper analyses the letters that the poet wrote during his long exile. In them, the poet, demonstrating a cultural awareness that has earned him the title of “pre-humanist”, emulates different literary styles. His letters of exile deliberately recall the most famous exiled poet of classical times, Ovid, and borrows from the vocabulary, style and psychology of Ovid’s Tristia and Epistulae ex Ponto to express his own anguish in the twilight years of his life.
Keywords: Exile; Chioggia; Ovid; Prehumanism; Autobiography